The Influence Of Education Level And Job Training Levels in The Performance Of State Civil Servent The Inspektrorat Riau Province - Sosiady, Mulia (Basecamp Economics PubMed, 2024)
This study was conducted at the Inspectorate of Riau Province with the objective of examining the influence of educational attainment and job training on employee performance at the regional Inspectorate of Riau Province. The sampling method employed was random sampling, with a total of 60 respondents. The R-squared value obtained from the data analysis is 0.544, indicating that the level of education and job training collectively account for 54% of the improvement in employee performance. The remaining 46% is influenced by factors not included in this study. The findings of this study demonstrate that education and job training are significant factors in enhancing employee performance in government agencies. However, it is important to recognise that there are other variables that also contribute to the overall performance of employees.